Cancer stem cells: Mediators of tumorigenesis and metastasis in head and neck squamous cell carcinoma. Issue 3 (25th March 2014) - Chinn, Steven B.; Darr, Owen A.; Owen, John H.; Bellile, Emily; McHugh, Jonathan B.; Spector, Matthew E.; Papagerakis, Silvana M.; Chepeha, Douglas B.; Bradford, Carol R.; Carey, Thomas E.; Prince, Mark E. P.
ABSTRACT Background Cancer stem cells (CSCs) represent a subpopulation of cells responsible for tumor growth. Their role in head and neck squamous cell carcinoma (HNSCC) tumorigenesis and metastasis remains uncertain. Methods Wound healing and an orthotopic animal model were used to study cells expressing the CSC phenotype (CD44high and aldehyde dehydrogenase [ALDH]+) and assess mobility, tumorigenesis, and metastasis. A prospective collection of 40 patient‐derived primary HNSCC specimens were analyzed for CSC‐proportion compared to clinical variables. Results CSCs exhibited significantly faster wound closure and greater tumorigenesis and regional metastasis in vivo than non‐CSCs. In primary patient tumors, size and advanced stage were correlated with elevated proportion of CSCs, however, not with survival. Conclusion HNSCC stem cells mediate tumorigenesis and regional metastasis in vivo. In primary patient tumors, CSC‐proportion was associated with tumor size and stage, but not with metastatic spread or survival. CSC burden alone may only represent a minor variable in understanding CSCs and metastasis. © 2014 Wiley Periodicals, Inc. Head Neck 37: 317–326, 2015